2003
DOI: 10.1136/jnnp.74.7.929
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of external ventricular drainage infection: results of a prospective study

Abstract: Objectives: The aim of this study was to evaluate the influence of total drainage time on the risk of catheter infection, and the predictive value of standard laboratory examinations for the diagnosis of bacteriologically recorded cerebrospinal fluid (CSF) infection during external ventricular drainage. Methods: During a three year period, all patients of the neurosurgical intensive care unit (ICU), who received an external ventricular drain, were prospectivly studied. Daily CSF samples were obtained and exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
77
2
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(93 citation statements)
references
References 19 publications
9
77
2
5
Order By: Relevance
“…In one of the study it was demonstrated that hemorrhagic CSF -as a consequence of SAH or intraventricular hemorrhage (IVH) -occurred four times more frequently with a group of infected patients compared to the non-infected group [15]. Additionally the potential effect of SAH and IVH on the infection rate was mentioned in some of the later studies [7,[16][17][18][19]. Within our study the correlation between SAH and higher incidence of infections proved to be significant.…”
Section: Discussionmentioning
confidence: 65%
“…In one of the study it was demonstrated that hemorrhagic CSF -as a consequence of SAH or intraventricular hemorrhage (IVH) -occurred four times more frequently with a group of infected patients compared to the non-infected group [15]. Additionally the potential effect of SAH and IVH on the infection rate was mentioned in some of the later studies [7,[16][17][18][19]. Within our study the correlation between SAH and higher incidence of infections proved to be significant.…”
Section: Discussionmentioning
confidence: 65%
“…Pfisterer and colleagues 18 performed a transversal analysis of CSF results for 130 patients with external drainage from whom daily CSF samples were obtained. The leukocyte counts were heterogeneous in both the patient group and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Existe farta literatura sobre as complicações infecciosas 1,3,4,[9][10][11]15,18 , mas o assunto foge aos objetivos deste trabalho. Entretanto, a literatura sobre os problemas mecânicos de bolsas de drenagem é relativamente escassa, talvez porquê o mais grave deles, que é a hiperdrenagem liquórica, ocorra devido ao manuseio incorreto do sistema de derivação externa, e talvez esse fato não seja comum em países desenvolvidos, mas ocorre com freqüência em países de terceiro mundo.…”
Section: Discussionunclassified